Increasing Competitiveness In UMKM Momala Candle Studio: Digital Marketing Strategy And International Shipping (Meningkatkan Daya Saing UMKM Momala Candle Studio: Strategi Pemasaran Digital dan Pengiriman Internasional) - Melissa, Melissa; Zai, Immanuel (Indonesia Berdaya, 2025)
Momala Candle Studio, a micro, small, and medium enterprise (MSME) in Batam, produces aromatherapy candles that are highly attractive to foreign tourists. The challenges faced include a lack of effective digital marketing strategies and insufficient understanding of international shipping procedures. The aim of this research is to expand Momala Candle Studio's market reach, enhance product exposure among local and international audiences, and improve the competitiveness of the business. The research methods include observation and interviews. The implementation results indicate an increase in product exposure, access to international markets, and customer satisfaction.Abstrak: Momala Candle Studio, sebuah usaha mikro, kecil, dan menengah (UMKM) di Batam, memproduksi lilin aromaterapi yang sangat diminati wisatawan mancanegara. Tantangan yang dihadapi antara lain kurangnya strategi pemasaran digital yang efektif dan pemahaman yang kurang mengenai prosedur pengiriman internasional. Tujuan dari penelitian ini adalah untuk memperluas jangkauan pasar Momala Candle Studio, meningkatkan eksposur produk di antara khalayak lokal dan internasional, dan meningkatkan daya saing bisnis. Metode penelitian meliputi observasi dan wawancara. Hasil implementasi menunjukkan peningkatan eksposur produk, akses ke pasar internasional, dan kepuasan pelanggan.